Association Between Abrupt Change to Teleworking and Physical Symptoms During the Coronavirus Disease 2019 (COVID-19) Emergency Declaration in Japan. Issue 1 (January 2022) - Tezuka, Masato; Nagata, Tomohisa; Saeki, Kenta; Tsuboi, Yamato; Fukutani, Naoto
Abstract : Objective: We investigated the association between telework frequency and the presence of non-COVID-19–related physical symptoms during the COVID-19 emergency declaration among workers in Japan. Methods: Data were collected from 1648 workers via web-based self-reported questionnaires. Multivariate logistic regression models were used to investigate the association between telework frequency per week (0, 1–2, 3–4, and ≥5 days/week) and the presence of stiff shoulders, eyestrain, and low back pain. Results: Among 917 participants, telework frequency was significantly associated with stiff shoulders (≥5 days: adjusted odds ratio [aOR] 3.02, 95% confidence interval [CI] 1.37–7.06), eyestrain (≥5 days: aOR 5.31, 95% CI 2.09–13.44), and low back pain (≥5 days: aOR 5.57, 95% CI 2.22–14.00), compared with non-teleworkers. Conclusions: Workers who abruptly began telework experienced more physical symptoms than non-teleworkers during the emergency declaration.